O fenômeno da variável da concordância verbal nas produções textuais dos alunos do ensino médio: uma intervenção sociolinguística - SÁ, Claudia Martins de (2018)
In this paper ―THE PHENOMENON OF THE VERBAL AGREEMENT VARIABLE IN TEXTUAL PRODUCTIONS OF STUDENTS OF MIDDLE SCHOOL: A Sociolinguistic intervention", has as main objective to systematize a didactic-pedagogical proposal for a grammar teaching that considers the language in use. First of all, we analyze how this grammatical phenomenon manifests itself in seventy-eight essayargumentative texts written by students of the 3rdgrade of high school CE Vinícius de Moraes, a public school inthe city of São Luís – Maranhão – Brazil. The analysis was performed according to the principles of William Labov (2008 [1972]) and Stella Maris Bortoni Ricardo (2004, 2005), working with the empirical method, applied to a qualitative and exploratory approach through interventionist action research. In the texts were diagnosed deviations of verbal agreement in which students do not properly use the third person plural, conditioned by structural factors. Of the elements of linguistic character, phonic salience and the position of the subject in relation to the verb are significant. From the results, we elaborate and apply a sequence of activities on verbal agreement, supported by sociolinguistic principles. For the referrals, guidelines and suggestions on grammar teaching, we used the support of Franchi (2006), Vieira and Brandão (2011), Faraco (2008), Martins (2013) and Martins and Tavares (2013). After applying the didactic sequences on verbal agreement, the students confirmed that the relations of agreement became more comprehensible, this fact was proven from the students' rewrites, as well as the reflection they carried out during the activities developed.